Children's music in the development of scientific inquiry - Huaman Santos, Carmen Veronica (2023)
Science teaching is a key issue and is a necessity for people, efforts to work in this area are still insufficient because children do not show interest in it despite their investigative abilities. The purpose of this research is to propose workshops based on children's music to promote the development of scientific inquiry in children of three years of an initial educational institution of Chiclayo. It has a quantitative approach methodology with a proactive, non-experimental descriptive design. As a result, it was identified that those evaluated are at low and medium levels, so it is vitally important to serve them through a didactic and innovative proposal. In short, it is stated that active learning workshops accompanied by children's music constitute a powerful tool to develop scientific inquiry in early childhood.